Aerodynamic Loads On Rotor Blades - Abedi, Hamidreza (My University, 2011)
In the last decade, we have heard more and more about the need of renewable clean energy, but not much has been done. Currently, the wind power energy is the most popular of all of these green technologies. Thousands of wind turbines are being invested and installed everywhere worldwide. Thus, many questions arise. The aerodynamic loads on the rotor blades are the largest loads acting on a wind turbine. The horizontal wind turbine types of blades are usually made of two or three airfoils such as a propeller. In these types of blades, it is the lift force which makes the rotor turn. The drag force acts perpendicular to the lift force due to the resistance of the airfoil from the wind and counteracts the rotation to rotor. Therefore, predicting these loads accurately is one of the most important parts of the calculations in wind turbine aerodynamics. Another reason for computing the aerodynamic loads on rotor blades is to model the aeroelastic response of the entire wind turbine construction. There are different methods to calculate the aerodynamic loads on a wind turbine rotor with different level of complexity such as Blade Element Momentum Method (BEM), Vortex Method, Panel Method and Computational Fluid Dynamics (CFD). Most aerodynamic codes use BEM (together with many additions) which is very fast and gives fairly accurate results. The main goal of this project is studying the Helical Vortex Method. In this text, helical vortex method has been developed and compared with Blade-Element Momentum (BEM) theory for the analysis of wind turbine aerodynamics.
Keywords: Energi; Hållbar utveckling; Strömningsmekanik; Energy; Sustainable Development; Fluid mechanics